Peran Orang Tua dalam Mencegah Pergaulan Bebas di Kalangan Pelajar (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Free association among students is a social problem that often occurs in Indonesia. One of the contributing factors is the lack of parents' role in supervising and guiding their children. This study aims to analyze the role of parents in preventing promiscuity among students. This research uses qualitative research methods with data collection techniques through interviews and observation. The research subjects were 10 parents of students at a high school in Makassar. The data obtained were then analyzed using thematic analysis techniques. The results of the study show that parents play an important role in preventing promiscuity among students. Schools also have a role, although not as big as the role of parents, this is because schools have programs free of bullying and sexual harassment so that they are considered to have contributed to building and shaping the character of students who are not easily drawn into promiscuity. Parents who are active in supervising their children and provide clear direction regarding applicable social norms are able to prevent their children from falling into promiscuity. In addition, parents also play a role in providing guidance on the importance of maintaining reproductive health and strengthening religious and moral values ​​to their children. In conclusion, this study shows that the role of parents in preventing promiscuity among students is very important. Therefore, there is a need for support from schools and the community in educating parents about the importance of their role in preventing promiscuity among students.